Teachers’ Reception of Technology for Professional Competence: Overcoming Barriers in Junior High Schools - Iraningsi, Rini Ilma; Hizir, Hizir; Bahrun, Bahrun; Desmi, Desmiri (Edukasi, 2026)
Technology integration in schools continues to face challenges related to inadequate infrastructure, unstable internet connectivity, and gaps in teachers’ digital competencies. This study aims to explore teachers’ perceptions and acceptance of technology use in enhancing professional competence amid these constraints in junior high schools. Employing a descriptive qualitative design, the study was conducted at SMPN 1 Salang and SMPN 4 Salang, Simeulue Regency, over a three-month period. Eight participants, including principals, teachers, and school administrators, were selected using purposive sampling based on their direct involvement in educational technology use. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using thematic analysis involving data reduction, data display, and conclusion drawing. The findings revealed that teachers’ reception of technology is reflected in three key aspects: participation in technology-based training, shifts in attitudes from resistance to acceptance, and self-initiated learning activities. Despite these positive responses, teachers’ efforts remain constrained by limited technological facilities, uneven internet access, and varying levels of digital literacy. The study concludes that positive teacher reception plays a crucial role in strengthening professional competence, although sustained institutional support through continuous training, supportive policies, and infrastructure development is essential to optimize technology integration in schools.